What predicts the use of interaction-oriented pedagogies? The role of self-efficacy, motivation, and employment stability. (July 2022) - Orona, Gabe Avakian; Li, Qiujie; McPartlan, Peter; Bartek, Carrie; Xu, Di
Abstract: In this study we investigate college instructors' use of practices that facilitate interactions in online college courses. We begin by drawing on several strands of literature to offer a person-purpose interaction framework with two dimensions – one regarding the entities involved in the interaction (instructor, student, content) and the other regarding the pedagogical goal of the interaction (academic, social, managerial) – that result in six sub-domains of practices. Subsequently, we examine the frequency of, and factors associated with instructors' use of these six domains, using survey data collected from online college instructors (N = 126) from a large community college. The results show that instructors using more interaction-oriented practices consistently have greater employment stability and teaching load, greater self-efficacy for using learning management systems, and greater perceived benefits of online learning for students. The findings have several implications for future research examining pedagogical behavior, as well as the design of professional development activities aimed at enhancing the use of effective online instructional practices among college instructors. Highlights: A novel person-purpose framework for understanding online pedagogy is introduced. Instructor self-efficacy relates to greater use of interaction-oriented practices. Student-centered motivation relates to greater use of interaction-oriented practices. Employment stability relates to greater use of interaction-oriented practices. Implications for enhancing adoption of effective online pedagogy is discussed.